Retention and annealing in solid CsIO3 activated with fast neutrons - Dupetit, Gustavo Alberto; Aten, A. H.W. Jr. (Elsevier BV, 1967)
Fil: Dupetit, Gustavo Alberto Comisión Nacional de Energía Atómica; Argentina